A "Proteoglycan Targeting Strategy" for the Scintigraphic Imaging and Monitoring of the Swarm Rat Chondrosarcoma Orthotopic Model. (6th February 2011) - Peyrode, Caroline; Gouin, François; Vidal, Aurélien; Auzeloux, Philippe; Besse, Sophie; Dauplat, Marie-Mélanie; Askienazy, Serge; Heymann, Dominique; Chezal, Jean-Michel; Redini, Françoise; Miot-Noirault, Elisabeth
Abstract : Our lab developed 99m Tc-NTP 15-5 radiotracer as targeting proteoglycans (PGs) for the scintigraphic imaging of joint. This paper reports preclinical results of 99m Tc-NTP 15-5 imaging of an orthotopic model of Swarm rat chondrosarcoma (SRC). 99m Tc-NTP 15-5 imaging of SRC-bearing and sham-operated animals was performed and quantified at regular intervals after surgery and compared to bone scintigraphy and tumoural volume. Tumours were characterized by histology and PG assay. SRC exhibited a significant 99m Tc-NTP 15-5 uptake at very early stage after implant (with tumour/muscle ratio of 1.61 ± 0.14), whereas no measurable tumour was evidenced. As tumour grew, mean tumour/muscle ratio was increased by 2.4, between the early and late stage of pathology. Bone scintigraphy failed to image chondrosarcoma, even at the later stage of study. 99m Tc-NTP 15-5 imaging provided a suitable set of quantitative criteria for the in vivo characterization of chondrosarcoma behaviour in bone environment, useful for achieving a greater understanding of the pathology.